Modern Lifestyle and Diseases - Beknazarovna, Abduraimova Shakhrioda; Mamatkulovich, Kenjaev Yodgor (American Journal of Bioscience and Clinical Integrity, 2025)
In this article, we will discuss how working under difficult conditions affects human brain functions and what neuropathological diseases it can lead to, as well as the consequences of video game addiction in adolescents. We will also review several neurological diseases.